2014
DOI: 10.5114/aoms.2013.34317
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing quality of life in patients during radiotherapy for head and neck cancer

Abstract: IntroductionRadiotherapy (RT) in combination with chemotherapy is a standard of care for patients with head and neck squamous cell carcinoma (HNSCC). The RT is associated with side effects, which impact on quality of life (QoL). Thus, the aim of this prospective longitudinal study was to investigate the impact of RT on the QoL of patients with HNSCC during RT.Material and methodsFrom September 2008 to February 2010, 205 patients with locally advanced HNSCC were enrolled. The data pertaining to their QoL were c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
24
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 24 publications
9
24
0
5
Order By: Relevance
“…There are conflicting reports on the associations between demographic and clinical characteristics and QOL in previous studies, and a number of studies found no associations. Among those that did, age seemed to be related to different QOL aspects; younger patients reported better physical functioning but poorer emotional functioning, global health status, and overall QOL . Being unmarried, having less social support, unemployment, smoking, and alcohol abuse were associated with poorer QOL in previous studies, whereas conflicting results were reported for the effect of education and socioeconomic status .…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…There are conflicting reports on the associations between demographic and clinical characteristics and QOL in previous studies, and a number of studies found no associations. Among those that did, age seemed to be related to different QOL aspects; younger patients reported better physical functioning but poorer emotional functioning, global health status, and overall QOL . Being unmarried, having less social support, unemployment, smoking, and alcohol abuse were associated with poorer QOL in previous studies, whereas conflicting results were reported for the effect of education and socioeconomic status .…”
Section: Introductionmentioning
confidence: 81%
“…Among those that did, age seemed to be related to different QOL aspects; younger patients reported better physical functioning but poorer emotional functioning, global health status, and overall QOL . Being unmarried, having less social support, unemployment, smoking, and alcohol abuse were associated with poorer QOL in previous studies, whereas conflicting results were reported for the effect of education and socioeconomic status . In terms of clinical characteristics, tumor site, advanced stage of disease, comorbidity, lower physical functioning, and having a feeding tube or tracheostomy were associated with decrements in different QOL dimensions.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Although gender is not commonly considered a predictive variable for QOL or symptoms burden, previous studies have shown that the female gender has a negative influence on QOL and emotional distress . However, the results of our study and previous studies may be related to the unequal distribution of gender, which creates a site and treatment effect; moreover, the symptoms scores for anxiety and depression utilized for this analysis were based on the two‐question version. Although these tools have been validated, more variability in scores may have been seen if the full version was provided to each survivor.…”
Section: Discussionmentioning
confidence: 63%
“…2 As the unique approved treatment agent for pancreatic cancer in clinical, unfortunately, gemcitabine show poor efficacy, drug resistance, and side effects. [3][4][5] It is desired to develop effective methods to improve the therapeutic efficacy in clinic.…”
mentioning
confidence: 99%